Mobile application for automobile security system - Suaysom, Ittipon; Adsavakulchai, Suwannee (Engineering and Applied Science Research, 2014)
This paper presents the application of the mobile phone as a remote control for motor vehicle to open-close the door. This security system uses a wireless network to receive the information and transmits it to the motor vehicle. A user uses a communication device, such as a Bluetooth (ESD200) in mobile phone, to send instructions to the wireless network. The research idea focuses on the users into authorized ones by simulation. Firstly, to develop the embedded system into a security system is to identify the authorized drivers in response to the real time. A microcontroller (ET-BASE PIC18F8722 (ICD2)) is installed in the car for transmitter Bluetooth in mobile phone using Python, Paraniwin and MPlab program to interface that is complete and showing on the mobile phone screen that is available. Finally, the experimental results verify that the proposed method is valid and useful against the vehicle thefts problem with a success rate of 100% within surrounding distance12 meters within 5 seconds then the door opening intrusion message (SMS) alert via mobile phone. It can be concluded that the security system is efficient, easy to use and economical.